Mediators and theories of change in psychotherapy for young people with personality disorders: a systematic review protocol - Volkert, Jana; Taubner, Svenja; Barkauskiene, Rasa; Mestre, Jose M.; Sales, Célia M. D.; Thiele, Vanessa; Saliba, Andrea; Protić, Sonja; Adler, Asta; Conejo-Cerón, Sonia; Di Giacomo, Dina; Ioannou, Yianna; et al. (Frontiers in psychology, 2021)
Background: Personality disorders (PDs) are a severe health issue already prevalent among adolescents and young adults. Early detection and intervention offer the opportunity to reduce disease burden and chronicity of symptoms and to enhance long-term functional outcomes. While psychological treatments for PDs have been shown to be effective for young people, the mediators and specific change mechanisms of treatment are still unclear.Aim: As part of the “European Network of Individualized Psychotherapy Treatment of Young People with Mental Disorders” (TREATme), funded by the European Cooperation in Science and Technology (COST), we will conduct a systematic review to summarize the existing knowledge on mediators of treatment outcome and theories of change in psychotherapy for young people with personality disorders. In particular, we will evaluate whether mediators appear to be common or specific to particular age groups, treatment models, or outcome domains (e.g., psychosocial functioning, life quality, and adverse treatment effects).Method: We will follow the reporting guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement recommendations. Electronic databases (PubMed and PsycINFO) have been systematically searched for prospective, longitudinal, and case-control designs of psychological treatment studies, which examine mediators published in English. Participants will be young people between 10 and 30years of age who suffer from subclinical personality symptoms or have a personality disorder diagnosis and receive an intervention that aims at preventing, ameliorating, and/or treating psychological problems.Results: The results will be published in a peer-reviewed journal and at conference presentations and will be shared with relevant stakeholder groups. The data set will be made available to other research groups following recommendations of the open science initiative. Databases with the systematic search will be made openly available following open science initiatives. The review has been registered in PROSPERO (evaluation is pending, registration number ID 248959).Implications: This review will deliver a comprehensive overview on the empirical basis to contribute to the further development of psychological treatments for young people with personality disorders.
Gesehen am 09.12.2021